Failing forward in Economic and Monetary Union: explaining weak Eurozone financial support mechanisms. Issue 10 (3rd October 2021) - Howarth, David; Quaglia, Lucia
ABSTRACT: In this article, we apply the 'failing forward' approach to analyse the negotiations on and design of reforms to Eurozone economic governance to tackle the Covid-19-related crisis of Economic and Monetary Union (EMU). This crisis highlights both spill-overs from major asymmetries in EMU and weaknesses in the incomplete economic governance of the Eurozone. We focus on the financial support mechanisms agreed upon after intergovernmental negotiations in major crisis situations. These reforms represent compromise solutions that reflect well-entrenched disagreements among member states. We explain why more far-reaching reforms to Eurozone economic governance – notably, the adoption of mutualized Euro-denominated debt and the generalized use of grants over loans – have not been adopted, despite the severity of the Covid-19-related crisis. These reforms – notably the Next Generation European Union (NGEU) financial package adopted in July 2020 – fail to address and, rather, contribute to existing asymmetries, thus sowing the seeds of future crises.